2008
DOI: 10.3177/jnsv.54.142
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrimidine Tract-Binding Protein Is Involved in Regulation of Albumin Synthesis in Response to Food Intake

Abstract: Summary Our recent study demonstrates that polypyrimidine tract-binding protein (PTB), which is a sequence specific RNA-binding protein, attenuates albumin synthesis in a cell-free translation system. In this study, the effects of food intake on regulation of albumin synthesis through binding of PTB to albumin messenger RNA (mRNA) were investigated. Rats were divided into 1 of 3 groups: fed; fasted for 36 h; or fasted for 36 h and then refed for 24 h. No significant differences in albumin mRNA levels were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…(17,2022) Conversely, our previous study showed that phosphorylation of ribosomal protein S6 could be detected through mTOR signaling in the livers of rats fed freely. (23) To the best of our knowledge, the present results comprise the first reported evidence that continuous supplementation with BCAAs induced phosphorylation of ribosomal protein S6 in the livers of rats with chronic liver disease.…”
Section: Discussionsupporting
confidence: 51%
“…(17,2022) Conversely, our previous study showed that phosphorylation of ribosomal protein S6 could be detected through mTOR signaling in the livers of rats fed freely. (23) To the best of our knowledge, the present results comprise the first reported evidence that continuous supplementation with BCAAs induced phosphorylation of ribosomal protein S6 in the livers of rats with chronic liver disease.…”
Section: Discussionsupporting
confidence: 51%
“…We concluded that the quantity of the added cystine was not suitable for mice, and their albumin synthesis in the liver was reduced. It is necessary in a future study to measure the albumin mRNA expression and other gene mRNA expressions which affect albumin synthesis in the liver (32).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, the albumin 3′-UTR contains an intron that improves mRNA processing. However, in addition to that, it also contains two pyrimidine-rich stretches known to bind PTB [58]. PTB is a ubiquitously expressed mRNA binding protein that serves as a common mediator of mRNA stability.…”
Section: Expression Cassette Designmentioning
confidence: 99%